PSYCHOLOGICAL DYNAMICS IN STIMULATING CREATIVITY AND INNOVATION IN ENTREPRENEURIAL ENVIRONMENTS - Purnomo, Yudiyanto Joko; Rosadi, Andri Asoka Sidantara (PT. LITERASI SAINS NUSANTARA, 2024)
In the rapidly changing business world, creativity and innovation are foundational to the success of a company, especially in the context of entrepreneurship. The ability to think outside the box, create new solutions, and identify market opportunities are key factors that differentiate successful businesses from those that fail. This research aims to analyze the psychological dynamics in stimulating creativity and innovation in the entrepreneurial environment. The research method used is a qualitative literature review using data from Google Scholar from 2007 to 2024. The study results indicate that psychological dynamics play a crucial role in stimulating creativity and innovation in entrepreneurial environments. Understanding motivation, perception of failure, and supportive work environments are key to creating conditions that enable entrepreneurs to create new value, discover innovative solutions, and bring about significant change. Entrepreneurship requires more than just business knowledge; it also requires sensitivity to the psychological factors influencing creativity and innovation.